2022
DOI: 10.1038/s41419-022-04677-0
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-associated circRNA circATG7 facilitates autophagy and promotes pancreatic cancer progression

Abstract: Dysregulation of autophagy and circular RNAs (circRNAs) are involved in the pancreatic cancer (PC) progression. However, the regulatory network between circRNAs, autophagy, and PC progression remains unknown. Herein, we demonstrated that autophagy-associated circRNA circ-autophagy related 7 (circATG7) was elevated in PC tissues compared to adjacent tissues, and in PC cells treated with EBSS and hypoxia. circATG7 expression was positively associated with tumor diameter and lymph node invasion in patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Another 149 studies were removed for not being related to PC or circRNAs, or not providing sufficient data. Ultimately, a total of 48 papers were included in our meta-analysis, including 34 on prognosis [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], 11 on diagnosis [ 29 , 30 , 31 , 48 , 55 , 56 , 60 , 61 , 62 , 63 , 64 ], and 30 on relationship with clinicopathological features [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ,…”
Section: Resultsmentioning
confidence: 99%
“…Another 149 studies were removed for not being related to PC or circRNAs, or not providing sufficient data. Ultimately, a total of 48 papers were included in our meta-analysis, including 34 on prognosis [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ], 11 on diagnosis [ 29 , 30 , 31 , 48 , 55 , 56 , 60 , 61 , 62 , 63 , 64 ], and 30 on relationship with clinicopathological features [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ,…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia is the widely accepted stimulator of autophagy induction via HIF-1-mediated expression regulation of key genes associated with autophagy, including adenovirus E1B 19 kDa-interacting protein 3 (BNIP3), BNIP3-like (BNIP3L), ATG9A, PIK3C3, Beclin 1, ATG5 and ATG7 (39)(40)(41)(42)(43). Increased BNIP3 and BNIP3L expression induced by HIF-1, can disrupt the Bcl-2-Beclin1 complex to initiate autophagy (41).…”
Section: Autophagy and Hypoxiamentioning
confidence: 99%
“…In addition, hypoxia activates the AMP/AMPK/mTOR pathway and inhibits the PI3K/AKT/mTOR pathway to initiate autophagy ( 44 , 45 ). Through intrinsic cytoprotective pathways, hypoxia-induced autophagy enhances tumor cell survival and contributes to the formation of the immunosuppressive TME that fuels tumor growth ( 39 , 40 , 46 , 47 ). For example, HIF-1-dependent autophagy was crucial in inhibiting CTL and NK cell-mediated anti-tumor immune responses ( 47 , 48 ).…”
Section: Autophagy Involved In Tmementioning
confidence: 99%
“…Subsequent experiments demonstrated that circRHOBTB3 sponged miR-600 to upregulate the NACC1 expression, which further activated the Akt/mTOR pathway to induce cell autophagy. Meanwhile, He et al (2022) discovered upregulation of circATG7 in PDAC tissue, which stabilized autophagy-related 7 (ATG7) mRNA by recruiting HUR and sponging miR-766-5p, a suppressor of ATG7 mRNA, thus increasing the expression of ATG7, which promotes the autophagy process.…”
Section: Main Textmentioning
confidence: 99%